Validity of DIPSI criteria performed during early mid- and late-pregnancy for diagnosis of gestational diabetes - Chauhan, Yashodhra; Abhichandani, Roshni; Malik, Saurabh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Gestational diabetes mellitus increases the risk of perinatal complications and chronic diabetes in the mother and child, and early detection and treatment could improve perinatal and long-term outcomes in GDM women and their offspring. Several criteria have been proposed for diagnosing GDM, but there is no universal consensus regarding the most accurate and feasible test acceptable to every sociodemographic region. This study was undertaken to evaluate the single-step non-fasting 75 gm Diabetes in Pregnancy Study Group of India (DIPSI) criteria of GDM performed during early (16-20 weeks) mid-(24-28 weeks) late-pregnancy (32-36 weeks), compared with the two-step fasting 100 gm glucose challenge through the ACOG recommended Carpenter Coustan criteria. Methods: It was a prospective study analyzing a cohort of pregnant women from the 16th week of gestation till the 36thth week, excluding previously known diabetic patients. All study participants were screened for GDM three times using the DIPSI criteria (between 16-20 weeks, 20-24 weeks and 32-36 weeks) and once using the 2-step ACOG criteria between 24-28 weeks. Results: The study includes 200 participants with a mean age of 27.14% of women were diagnosed with GDM based on the 2-step ACOG recommended criteria. The sensitivity, specificity and accuracy of DIPSI criteria during 16-20 weeks were 25%, 99.4% and 78.6%, respectively; during 20-24 weeks, sensitivity was 96.4%, specificity was 95.9%, and accuracy was 96.07%. The sensitivity, specificity and accuracy of DIPSI criteria during 32-36 weeks were 96.4%, 94.8% and 95.2%, respectively. Conclusions: DIPSI criteria is highly sensitive and specific and can accurately detect GDM between 24-28 weeks; it lacks sensitivity and is inaccurate in detecting GDM between 16-20 weeks of gestation. However, as these parameters are similar at 32-36 weeks, high-risk patients for GDM could be considered for rescreening during the third trimester.